Teaching English Based on Character Education at Senior High School Metro - Fenny Thresia (Bandar Lampung University (UBL), 2014)
Character education as the deliberate use of all dimensions of school life to foster optimal character development. The aim of this research to give a teaching model to English teacher at senior high school level in Metro especially in teaching English based on character education. This research and development study took subject from all six senior high school in Metro consist of six teachers who teach in tenth grader. This study focus on design and evaluation of teaching instrument. The result of this study show that most of teacher still confuse with character education in teaching and learning process in English subject because most of material in English book do not integrated character education. Therefore this study helps all English teachers to apply material with character education. The teacher is not only taught English material but also teach value and character building. It influences the students’ character in their daily life. Students become more polite, honest, diligent and religious